2023
DOI: 10.3390/ani13111848
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Genotype on Productivity and Egg Quality of Three Hen Strains Included in a Biodiversity Program

Abstract: The aim of the study was to evaluate the effect of genotype on the productivity and egg quality of three hen strains included in the genetic resource protection program in Poland. The study encompassed populations of laying hens, i.e., Rhode Island Red/RIR (R-11 and K-22) and Rhode Island White (A-33). The analysis over five generations included the basic production traits, i.e., the weight of the birds at 20 weeks (g), egg weights at 33 and 53 weeks, sexual maturity, the number of eggs laid up to 56 weeks of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 33 publications
2
3
0
Order By: Relevance
“…Similar results were also reported by other authors [Sokołowicz et al 2018, Fathi et al 2021 while in some works this trait in eggs of the commercial strains is reported at 25-26% [Wu et al 2007] or 25-27% [Wengerska et al 2023]. The Rhode Island Red and Rhode Island White breeds, used globally for laying production, have a yolk percentage as 26.5% of egg weight at the 33rd week of life [Calik and Obrzut 2023]. In unselected local Italian hen breeds, the yolk percentage per egg was 31.1% compared to 24.9% in commercial highproducing hybrids [Sirri et al 2018].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Similar results were also reported by other authors [Sokołowicz et al 2018, Fathi et al 2021 while in some works this trait in eggs of the commercial strains is reported at 25-26% [Wu et al 2007] or 25-27% [Wengerska et al 2023]. The Rhode Island Red and Rhode Island White breeds, used globally for laying production, have a yolk percentage as 26.5% of egg weight at the 33rd week of life [Calik and Obrzut 2023]. In unselected local Italian hen breeds, the yolk percentage per egg was 31.1% compared to 24.9% in commercial highproducing hybrids [Sirri et al 2018].…”
Section: Discussionsupporting
confidence: 86%
“…The parameters characterising shell quality of both breeds eggs were at a satisfactory level. Shell thickness decreases with birds' age [Sokołowicz et al 2018, Sokołowicz et al 2019, also a decrease in shell strength with age [Rodriguez-Navarro et al 2002, Sokołowicz et al 2019, Calik and Obrzut 2023 was confirmed. In the case of Polbar, a slight (but insignificant) decrease in shell thickness with age, but it was also observed that shell density and strength increased with age in this breed.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…They reported that high quantities of caffeine could eventually bring about shell fractures caused by calcium loss and availability. Finally, as commonly observed in laying hen husbandry [29], eggshells were thinner for light hens than for semi-heavy ones (370 vs. 386 µm, p = 0.038). In this sense, Silversides and Scott [44] found that the shell percentage in the egg was lower for ISA white hens than for ISA brown hens.…”
Section: Egg External Qualitysupporting
confidence: 69%
“…The genetics of laying hens and the diet consumed are the main sources of variation affecting egg production and quality [28,29]. Conventionally, two types of laying hens are used worldwide in laying hen husbandry: light hens (hens laying white eggs) and semi-heavy hens (hens laying brown eggs).…”
Section: Productive Performance Of Laying Hensmentioning
confidence: 99%